Improving Communication Delay of Outpatient Sleep Study Results to Pediatric Otolaryngology Patients and Families. (May 2019) - Ruda, James M.; Payne, Linda; May, Anne; Splaingard, Mark; Lemle, Stephanie; Jatana, Kris R.
Objective: We undertook this quality improvement project to improve communication of outpatient pediatric sleep study results to families in a consistent and timely manner. Methods: Based on the Institute for Healthcare Improvement quality improvement methodology, multiple key drivers were identified, including standardizing documentation and communication for sleep study results among the otolaryngology department, sleep center, and families. Meaningful interventions included developing standard electronic medical record documentation and utilizing otolaryngology nurses and advanced practice nurses to assist with communication by sending the results from the sleep center to both the referring otolaryngology provider and the triage nurses. The primary outcome measure was the monthly proportion of sleep studies communicated by the otolaryngology department to families within 3 business days. Results: Average monthly sleep study results communicated to families within 3 business days increased from 31% to 92.9% over the study period ( P < .0001). Sleep study results were personally communicated via telephone and voicemail in 60.88% and 34.0% of cases, respectively. Approximately 50.0% of families receiving voicemails later contacted our department for their children's study results. Discussion: Novel documentation strategies and involvement of our entire clinical team (physicians, nurses, and advanced practice nurses), allowed us to significantly improve the consistency and timeliness of our communication of outpatient sleep study results to families in a proactive manner. Implications for Practice: With time-sensitive clinical test results, such as those from pediatric sleep studies, intra- and interdepartmental collaboration and standardization of the communication process and documentation may allow for more expedient care of children with suspected obstructive sleep apnea.